Analisis Kinerja Alat Gali Muat Dan Alat Angkut Untuk Mencapai Target Produksi 20.000 Ton/Bulan Pada Penambangan Batu Kapur Di PT. Anugrah Halaban Sepakat, Kabupaten Lima Puluh Kota, Sumatera Barat - trihadma trihadma; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Anugrah Halaban Sepakat is a limestone mining company which is located in Laharkumbuh, fifty cities. In itsmining activities, the digging and loading equipment used by PT. Anugrah Halaban agreed is 1 unit of Volvo Pc 200 Excavatorand 2 units of Mitsubishi Colt Diesel 125 Ps Dump Truck. PT. Anugrah Halaban Agreed in area 1a set a limestone productiontarget of 20,000 tons / month, while the realization of limestone production in October was 11,067 tons. From the realizationdata, it can be concluded that limestone production in area 1a in October 2021 did not reach the target set by the company.Inorder for the limestone production target to run optimally, it is necessary to carry out a match factor analysis and furtherproductivity analysis regarding the working hours of the tool, look for causes and actions taken to achieve the target and makeimprovements to optimize the performance of the digging tool. One of the appropriate methods used in overcoming these problemsis the Overall Equipment Effectiveness (OEE) method which is a production process performance measurement tool that canmeasure various losses that occur and identify potential improvements. achieve production targets. After that, the fishbone methodwas used to find the cause and effect that caused the production to not be achieved, then an effort was made to improve the losstime which caused the reduction in the effective working hours of the digging tool that had been planned by the company with theapplication of the 5W + 1H technique. After analysis and improvement efforts, the match factor value was 1 of 0.41 and the totallimestone production on the Volvo Pc 200 Excavator was 72,982.31 tons and the Mitsubishi Colt Diesel 125 Ps Dump Truck was27,982.31 tons, which means it has reached the target. even exceeding the production target of 20,000 tons and the OEE value ofeach tool obtained by 61%, 27% and 26%. However, the OEE value is still < 85% of the world class standard OEE value, whichis 85% and there is still room for improvement.